Kemampuan Komunikasi Matematis dan Metakognitif Siswa SMP Pada Materi Lingkaran Berdasarkan Gender - Diandita, Elly Rizki; Johar, Rahmah; Abidin, Taufik Fuadi (Mathematics Education Journal, 2017)
The purpose of this research is to find the mathematical and metacognitive communication skills of junior high school students by gender. This research is a quantitative research. The population of this research is all students of class VIII SMP Negeri 1 Banda Aceh, SMP Negeri 9 Banda Aceh, and SMP Negeri 13 Banda Aceh with sample each 1 (one) class from each school. The data collection used is the test of mathematical communication ability and metacognitive questionnaire as well as interview from metacognitive question result. To find the difference of mathematical and metacognitive ability of students used T-test. The results of this study indicate that 1) there is no difference in mathematical communication ability of junior high students on gender-based material circle in the research sample; 2) there is no difference in mathematical communication ability of junior secondary students in gender-based circle material in each school being the research sample; 3) there was no difference in metacognitive ability of junior high school students in gender-based material circles in the study sample; 4) there is no difference in metacognitive ability of junior high school students in gender-based material circles in each school to be a research sample; 5) there is a strong relationship between mathematical communication ability with student’s metacognitive ability.